Opłaty, kary i podatki służące ochronie środowiska w Polsce na tle doświadczeń innych krajów europejskich - Ptak, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the role of charges and fines in Polish environmental policy. The revenues raised by these instruments are transferred to the earmarked funds. The funds use the revenues to provide financial assistance for investments and other projects to achieve environmental objectives. Polish experience differs from the experience with environmental taxes in west and north European countries where the majority of environmental taxes generally represent central or local budget revenues. There is growing interest in such taxes in Poland. The author emphasizes the need of changes in the Polish system of economic instruments used for environmental protection. These changes will provide for the simplification of the existing system.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 99-109